Applying lean Six Sigma for waste reduction in a bias tyre manufacturing environment - Anand Sasikumar; Padmanav Acharya; Malini Nair; Abdul Ghafar (Cogent Business & Management, 2023)
The main aim of the study is to improve the quality of bias tyres, reduce manufacturing waste, and increase the yield of the tyre manufacturing process in a leading tyre manufacturing company in South India. This paper aims to show how Lean Six Sigma tools can be used to address and tackle non-valued added activities. It is of concern to the top management that non-value-added activities in the value stream are increasing and affecting the financial performance of the business. One of the authors, who is pursuing research on identifying success factors of implementing lean in process industries in India, as part of his field study had interacted with people of different hierarchical levels of the company to unravel the main causes of the non-value added activities in the production process. Lean Six Sigma methodology (LSS) was applied and the problem was evaluated by the DMAIC method (Define, Measure, Analyze, Improve, and Control). The LSS Methodology was coupled with Analytic Hierarchy Process (AHP) to prioritize the causes of the waste. The actual name of the company is disguised for confidentiality, and the case is devised based on the initial findings of the study in a tyre-manufacturing firm. This paper provides some key insights into the adoption of Lean Six Sigma practices in an Indian tyre-manufacturing environment. Lean Six Sigma practices are still in the developing stages in tyre manufacturing environments, and this study is an attempt to apply these practices successfully in such manufacturing environments.
Keywords: 650; AHP; Bias tyre manufacturing; DMAIC; Lean manufacturing; LSS; Six Sigma